2024
DOI: 10.1155/2024/5723254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Front Total Toe-In Angle on Tire Wear and Emissions for a Light-Duty Vehicle

Riton Kumer Das,
Md. Abu Mowazzem Hossain,
Md. Tazul Islam
et al.

Abstract: An experimental investigation is carried out in this study to investigate the effect of wheel alignment, particularly the front total toe-in angle, on tire wear and emissions for a light-duty vehicle. Such investigations reveal that there is a substantial correlation among rolling resistance, energy consumption, tire wear, tire travel life, and the total toe-in angle of the front wheel. It is observed that the rate of loss in tire travel life with regard to a condition without misalignment is up to 98.33% when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As such incorrect settings can occur unnoticed, there is a risk that a vehicle will be driven on the road for long distances with increased tire wear. Das et al [69] carried out experiments with extreme tire misalignments. It was shown that not only did the tire wear increase, but the CO 2 , CO, and NO x also increased in the ICE vehicle due to the increased frictional resistance.…”
Section: Wheel Alignment Maintenancementioning
confidence: 99%
“…As such incorrect settings can occur unnoticed, there is a risk that a vehicle will be driven on the road for long distances with increased tire wear. Das et al [69] carried out experiments with extreme tire misalignments. It was shown that not only did the tire wear increase, but the CO 2 , CO, and NO x also increased in the ICE vehicle due to the increased frictional resistance.…”
Section: Wheel Alignment Maintenancementioning
confidence: 99%